Rancang Bangun Alat Pengering Pelepah Pisang(Menggunakan Metode Controller Chien Regulator I dan Chien Servo I Sebagai Tuning Kontrol PI) - Irianto Irianto; Suhariningsih Suhariningsih; Viviana Ratna Dewanti (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Bananas provide many health benefits because they have enough vitamin A for daily body vitamins. Benefits of bananas are not only found in the fruit alone. Banana stem is rarely used because it is considered not to have more benefits and is only considered as waste. However, banana stem can be transformed into various forms of beautiful crafts and high economic value. Banana banana is dried first before being processed into various handicrafts. The process of drying banana is very dependent on the weather conditions and the heat of the sun. Conventional banana drying process takes approximately 70 hours with a solar temperature of about 40oC. The solution to this problem is, design and manufacture a microcontroller based banana bum dryer using PI control to regulate the temperature and utilize the heater as an alternative heat source. This PI control uses Chien Regulator I and Chien Servo I tuning methods. In this Final Project, temperature and banana moisture content is measured. The control will adjust the exhaust fan when the temperature read by LM35 is displayed on LCD 4x20 for temperature monitoring. To adjust the AC-AC voltage controller voltage on the heater, depending on the angle of ignition of the TCA785 IC. DAC of Microcontroller ATMega16 will convert the digital data released microcontroller into analog voltage. The Kp and Ki values used are Kp = 5 and Ki 0.625 using Chien Regulator I method and Kp = 4,126 and Ki 0.414 using Chien Servo I method The drying process takes 16 hours with water content of 4.76% at ± 65oC using Chien Servo I method because the temperature response is more stable.